PENGEMBANGAN SNAKE AND LADDER GAME SEBAGAI MEDIA PEMBELAJARAN PADA MATA KULIAH VOCABULARY SEMESTER III UNIVERSITAS ISLAM BALITAR - Puspita Sari, Hesty; Sari Putri Hestiningrum, Yunita (Universitas Islam Balitar, 2019)
Vocabulary mastery of students, especially the third semester of university students, remains poor. Vocabulary is a basic component of learning English. According to Burhan Nurigiyantoro (2001: 213) vocabulary is word richness owned by a language. With vocabulary, students understand word meanings used in particular context that must be prepared since early age. This research aims at developing snake and ladder game as a learning media to teach vocabulary course to the third semester students of Universitas Islam Balitar. Given that vocabulary is crucial in learning English, this research is able to enhance students’ vocabulary mastery through web-based game that is accessible for them; therefore, they can master and use vocabulary correctly. This research adopted in-depth interview, questionnaire, and, observation to collect the data. The participants were the third semester students of Universitas Islam Balitar who learned vocabulary course. All the data obtained from different data collection methods were used to provide solutions of the problem. This research is expected to enhance the students’ vocabulary mastery. Materials packaged in a more interesting media will ease and boost the students’ learning of vocabulary without looking up in a dictionary or other books.